Konstrukcija slovenske nacije skozi medijsko naracijo - Pušnik, Maruša (Teorija in praksa, 1999)
The article deals with the defining and understanding national identity through media culture, respectively through texts, produced by the culture. Inthe text, the relation between nation-identity-media and above all media construction and interpretation of national identity are examined. The first part deals with describtion of the identity construction. A constructivist paradigm in particularly is determined as the basis for the interpretation of the management of national identity through media discourse. In this view the languages, articulated in several discourses, are important factors in identity construction, including the national one. In the second part, the focus is put on the relation between nation and ethnicity. At the same time, taking the constructivist paradigm as the starting point, the article attemptsto present media 'influence' on the construction of 'Slovenian national identity', using the method of textual analysis of chosen media texts. In other words, the article attempts to present the ways media prescribe such identity to the individuals.
Keywords: narod; people; narodna identiteta; etničnost; Slovenci; Slovenes; mass media; množični mediji; vpliv